TEACHING VOCABULARY THROUGH COOPERATIVE LEARNING METHOD AT ISLAMIC BOARDING SCHOOL - Siti Emma Rachmawaty; Nur Asik (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
The research discussed about teaching vocabulary through cooperative learning method. The objective of this research was to find out deeply the students’ vocabulary taught by using coopertive learning method. This research applied a quasi-experimental method consisted of two groups pre-test and post-test design. There were two variables in this research; the independent variable and dependent variable, the independent variable was teaching method, namely cooperative learning method (NHT), and dependent variable was the students’ vocabulary. The result of the data indicated that teaching vocabulary through cooperative learning method is effective to improve students vocabulary. The students were enjoy and active in learning process, they communicate actively not only with their friends but also with their teacher. Because in learning process students and teacher must work together.  Therefore, the writer suggests that teaching by using Cooperative Learning method (NHT) is effective way in teaching vocabulary.